Perubahan Sosial Ekonomi Masyarakat Muslim (Studi Pada Pedagang di Kawasan Kampus UINSU Tuntungan) - Faiz Afza Ihsan; Muhammad Safitrah; Fiqih Faras Syahara; Nurfadillah Munte; Yusva Fadillah Nst (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Social change is a process that occurs in society formed on the basis of influences based on social phenomena. Various The form of change that occurs will affect the social system, including values, attitudes and behavior of individuals or groups in society. This research aims to describe the public's perception of the existence of the North Sumatra State Islamic University (UINSU) Tuntungan and analyze the impact on business opportunities around the campus. This research is a qualitative descriptive study which aims to qualitatively describe the phenomena found at the research location. The research location was carried out around the UINSU Tuntungan campus, Pancur Batu District, Deli Serdang Regency. Respondents consisted of traders around the UINSU Tuntungan campus and community leaders. The results of the research show that the existence of UINSU higher education has had a positive impact on the Muslim community, in particular, namely firstly opening up business opportunities so that many workers are absorbed, both from the transportation and culinary fields, such as opening their own business or working for other entrepreneurs. Second, it creates motivation for local children to continue their education at the highest level, so that in the end they can develop their region.